When values fall short: The surprising roles of honesty-humility, emotionality, and conscientiousness on leadership effectiveness - Arifin, Johan; El Junusi, Rahman; Mubarok, Ferry Khusnul; Al-Ansyari, Ahmad Fuad; Fad, Mohammad Farid; Kurniawan, Cecep Soleh (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2025)
Building effective global leaders is crucial for an organization to remain competitive. While fundamental traits like personality have always been important in the context of leadership, the use of the HEXACO model in Indonesian organizational leadership development is relatively new. This research examines the impact of HEXACO traits on the leadership effectiveness of lecturers who also serve as academic leaders at one of Indonesia’s Islamic higher education institutions, which is ranked among the top 40 religious-based universities worldwide, according to uniRank 2024. A total of 147 valid responses were garnered and analyzed descriptively using Structural Equation Modelling (SEM) with AMOS. The results show that extraversion, agreeableness, and openness to experience positively influence leadership effectiveness, while honesty-humility, emotionality, and conscientiousness have no significant effect. Although honesty and humility are important values that support ethical behavior, global leaders require the ability to influence and adapt, be flexible, and be creatively innovative. Additionally, overly conscientious leaders tend to be inflexible and emotionally high-stress during critical moments, which makes them less dependable.